The first family with adult osteogenesis imperfecta caused by a novel homozygous mutation in CREB3L1. Issue 8 (17th June 2019) - Cayami, Ferdy K.; Maugeri, Alessandra; Treurniet, Sanne; Setijowati, Eva D.; Teunissen, Bernd P.; Eekhoff, Elisabeth M.W.; Pals, Gerard; Faradz, Sultana M.; Micha, Dimitra
Abstract: Background: Osteogenesis imperfecta (OI) is a clinically heterogeneous disease characterized by extreme skeletal fragility. It is caused by mutations in genes frequently affecting collagen biosynthesis. Mutations in CREB3L1 encoding the ER stress transducer OASIS are very rare and are only reported in pediatric patients. We report a large family with a novel CREB3L1 mutation, with severe adult clinical presentation. Methods: Clinical examination was performed on the family members. Next generation sequencing was performed for the causative genes for OI. The mutation was confirmed in other family members with Sanger sequencing. Results: A novel homozygous mutation in CREB3L1 was identified in the three affected patients. The parents and siblings who carry the mutation in heterozygous state were clinically unaffected. The three affected siblings, who were reported to have been born healthy, presented very severe progressive skeletal malformations and joint contractures but absence of common OI characteristics including blue sclerae, deafness, and dentinogenesis imperfecta. Resorption of a part of the humerus presumably associated with fracture nonunion and pseudarthrosis. Conclusion: We report a novel homozygous CREB3L1 mutation in a large Indonesian family; the homozygous affected members have survived to adulthood and they present a more severe phenotype than previously reported, expanding the clinical spectrum of OI for this gene. Abstract : Osteogenesis imperfecta is characterized by high bone fragility; mutations in the OI causative gene CREB3L1 are very rare and are previously reported only in three families. Homozygous mutations in the first two families led to perinatal lethal OI whereas in the third family the pediatric patient showed severe OI. We present a novel CREB3L1 mutation in a large Indonesian OI family in which the three homozygous patients have survived into adulthood despite the severe progressive nature of the disease.